Advancements in bioengineered and autologous skin grafting techniques for skin reconstruction: a comprehensive review - Jillian Dean; Cosima Hoch; Barbara Wollenberg; Justin Navidzadeh; Bhagvat Maheta; Anisha Mandava; Samuel Knoedler; Khalil Sherwani; Helena Baecher; Alina Schmitz; Michael Alfertshofer; Max Heiland; et al. (Frontiers in Bioengineering and Biotechnology)
The reconstruction of complex skin defects challenges clinical practice, with autologous skin grafts (ASGs) as the traditional choice due to their high graft take rate and patient compatibility. However, ASGs have limitations such as donor site morbidity, limited tissue availability, and the necessity for multiple surgeries in severe cases. Bioengineered skin grafts (BSGs) aim to address these drawbacks through advanced tissue engineering and biomaterial science. This study conducts a systematic review to describe the benefits and shortcomings of BSGs and ASGs across wound healing efficacy, tissue integration, immunogenicity, and functional outcomes focusing on wound re-epithelialization, graft survival, and overall aesthetic outcomes. Preliminary findings suggest ASGs show superior early results, while BSGs demonstrate comparable long-term outcomes with reduced donor site morbidity. This comparative analysis enhances understanding of bioengineered alternatives in skin reconstruction, potentially redefining best practices based on efficacy, safety, and patient-centric outcomes, highlighting the need for further innovation in bioengineered solutions.